2022
DOI: 10.47700/jiefes.v3i2.4779
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Memengaruhi Minat Sedekah Non Tunai

Abstract: In this modern era, the development of Islamic financial instruments has entered an era of increasing awareness from various parties. One of them is by participating in adapting technological developments in alms collection, in addition to making it easier for almsgivers to channel their donations, this strategy is expected to optimize the potential of ZIS in Indonesia. However, the factors that encourage interest in non-cash donations still need to be studied more deeply in order to improve the optimization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Meanwhile, other research results, such as that conducted by Rismantari (2020), show that religiosity has a partially significant effect on the decision to give sadaqah. However, several studies, such as Irawati and Fitriyani (2022) and Kurniaputri et al (2020), have found that religiosity does not significantly influence the decision to give sadaqah online. Based on previous research, the following can be formulated.…”
Section: Religiosity and Intentionmentioning
confidence: 97%
“…Meanwhile, other research results, such as that conducted by Rismantari (2020), show that religiosity has a partially significant effect on the decision to give sadaqah. However, several studies, such as Irawati and Fitriyani (2022) and Kurniaputri et al (2020), have found that religiosity does not significantly influence the decision to give sadaqah online. Based on previous research, the following can be formulated.…”
Section: Religiosity and Intentionmentioning
confidence: 97%
“…This study was aided by adjusting the inclusion of the TPB and UTAUT theories. Previous research on the payment of zakat utilizing technology, such as digital payments and mobile banking, used the TPB and TAM theories most often (Afandi, 2021;Ahwal, 2021;Hasyim et al, 2020;Irawati & Fitriyani, 2022;Ningtias & Nadya, 2022). In addition, this study aims to update how society has come to embrace technology and investigate how people might develop the essential habits to become technologically literate.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-one trillion is collected through non-ZPO (BAZNAS, 2021a). This happens because awareness alone is not enough without being facilitated with the suitable media and facilities in channeling zakat, infaq, and alms funds for muzakki and donors (Irawati & Fitriyani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…1.194 trillion and is predicted to continue to increase in the following year. Based on the research results of Irawati and Fitriyani (2022), non-cash alms associations always experience an increase every year. The collection of public funds in a non-cash manner in 2016 at kitabisa.com amounted to Rp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation